Numeracy E-Module with Edugame As A Support For Mathematics Learning for Sixth-Grade Elementary School Students - Meira Sagita; Petra Kristi Mulyani (Journal of Education Technology, 2023)
The Covid-19 pandemic has caused learning loss, one of which is in mathematics learning. Students enjoy technology products because of online learning, but schools must encourage teachers to make their own. This research aimed at developing a numeracy E-module with edugame. This type of research was developed using the ADDIE method to produce e-modules that can support less than optimal learning due to learning loss during the COVID-19 pandemic. The methods used to collect data were questionnaires and tests. Data collection instruments were in the form of questionnaires and test questions. Data analysis techniques used descriptive qualitative, quantitative, and inferential statistical analysis. The research results showed that this e-module was very suitable for use as a support for mathematics learning in sixth-grade elementary school because it received a validation score from media experts of 90.7% and material experts of 86.7% and a user response of 100%. Apart from that, based on the t-test, it showed differences in learning outcomes after students used the numeracy module with edugame. The n-gain test result was 80.3%. It can be concluded that this e-module influences and improves student learning outcome and it is suitable for learning.